KEBERADAAN DAN PEMANFAATAN TUMBUHAN OBAT LANGKA DI WILAYAH BOGOR DAN SEKITARNYA - Syamsul Hidayat (Media Konservasi, 2012)
Comparative studies and surveys to several medicinal plant gardens in Bogor area and national park areas adjacent to the Bogor have been done in 2006-2009. From these activitis a number of endangered medicinal plants at  Bogor were recorded. At least 12 endangered medicinal plants species found in the area of national parks and some of them have been developed in the medicinal plant gardens. Some species have multi-use such as Oroxylllum indicum, Symplocos odoratissima, and Alstonia scholaris. While it has not found a medicinal plant garden or nursery business in Bogor area to handle the cultivation of the species of endangered  medicinal plants Keywords: surveys, medicinal plant, endangered, Bogor